Ocena programów ochrony środowiska województwa na tle regionalnego modelu zrównoważonego rozwoju i ochrony środowiska Polski - Kistowski, Mariusz (The assessment of regional environmental protection schemes according to regional model of sustainable development & environmental protection in Poland, 2007)
The assessment of regional environmental protection schemes versus preferable trends in national environmental protection & sustainable development revealed a significant diversity in the level of documents’ preparation. Slightly different is the evaluation of the compliance of the structure of tasks and resources planned in the schemes for their execution with the needs of the regions in terms of environmental protection specified in the regional model of sustainable development and environmental protection in Poland [Kistowski 2003], The ones evaluated as correct, i.e. highly compliant in this respect include the programmes for provinces: Kujawsko Pomorskie, Lubelskie, Lubuskie, Podlaskie, Pomorskie, and Świętokrzyskie. The most incoherent ones with the needs are the tasks formulated in the documents prepared for provinces: Mazowieckie, Podkarpackie, and Śląskie. The most coherent were such activity fields as: naturę and landscape conservation, proecological forest management, and solid waste management (only for coherence of task financing).
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1190, s. 294-305